Short-term Evaluation of Water Sorption of Glass Ionomer Cements - Monadle R. Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The bonding of cement materials to enamel and dentin may be affected by dimensionalchanges which may be happened after water absorption of the cement when it is in water when the fillingused by the person. The aim of our research was to see how much water may be noticed inside preparedcements compared with those with other traditional cements.Method and materials: tow light-cured (1 and 2) and another two chemically-cured (4 and 5) wereprepared. Two types of cements used by the Iraqi dentists also used, first one light-cured (No.3) and the otherwas chemically-cured (No.6) . Thirty samples were produced having 4mm height and 9mm diameter. Fivesamples from each type of cement were prepared. Then we record the weight of each sample was recordedafter setting of the material before putting them in water using very. To remove water from the specimenmaterial a desiccator was used for one day. Samples were kept in water. After different immersing times of5,10,15,30, and 60 minutes, one, three, seven, ten day, and fourteen the weight of each sample was recorded.The value recorded for water absorbed was rounded to the nearest 0.1mg/cm2. Results: light-cured cementsabsorb more water than chemical-cured cements. The highest value was noticed for cement (5) then forcement number (2). The least value was noticed for cement number (3).Conclusion: cements cured by lightabsorbed more water than chemically-cured cements. Modifying cement´s powder components showed noeffect on water sorption, while liquid chemical composition showed noticable effect on water absorbedbythe tested cements